Efektivitas Media Pembelajaran Monopoli Berbasis Assure Terhadap Kemampuan Berpikir Kritis Peserta Didik - Nora Pramartasari; Rini Rita T. Marpaung; Arwin Achmad (Universitas Lampung, 2018)
This research aim was to know the effectiveness of the monopoly learning media based ASSURE in increasing students critical thinking of the second grade in SHS. The design used was a pretest-posttest not equivalent. The research samples were the students of MIA I and MIA III amounted of 65 students that were selected through purposive sampling technique. The data of this research were qualitative and quantitative. Qualitative data were average value of students critical thinking ability were based on the instrument and then analyzed descriptively. Quantitative data were obtained from N-Gain, average value of the pretest, posttest, and then analyzed statistically using test 0.05 confidence level in the U. The results showed that the students in experiments class have average achievement score in the critical thinking with the category